ARCHITECTURAL MODELLING PATTERNS FOR SYSTEMS OF SYSTEMS. Issue 3 (21st November 2016) - Claire, Ingram; Richard, Payne; John, Fitzgerald
ABSTRACT: Architectural properties are amongst the defining features of systems of systems (SoS) – including distribution of the constituent parts, their autonomy, long lifecycles and unsynchronized evolution. In addition, SoS engineers need to consider the integration of legacy constituent parts, reason about the emergent behaviour of the SoS, determine the level of centralised control, and support resilience and fault tolerance. These are all features which can be tackled at least partially through architectural patterns. In this article, we present three example patterns previously identified in SoS. Patterns like these can also be used as a mechanism for transferring lessons learned in one SoS application domain into another domain. For each pattern presented, we highlight features that address the challenges posed by SoS. Finally, we detail ongoing efforts with the INCOSE Systems of Systems and Patterns Working Groups to prioritise future work in this area.